Mental health help-seeking intentions: The role of personality traits in a sample of college students - Shabrina, Arina; Siswadi, Ahmad Gimmy Prathama; Ninin, Retno Hanggarani (Psikohumaniora: Jurnal Penelitian Psikologi, 2022)
Many college students with mental health problems do not seek help. One of the predisposing factors that influences mental health help-seeking is personality traits. This study aims to explore the role of such traits in the mental health help-seeking intention of college students. It is a cross-sectional study using the correlational method. An online survey employing convenience sampling technique was completed by 480 participants. The survey covered demographic data, the Big Five Inventory, and a mental health help-seeking intention questionnaire. The data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and multivariate regression analysis. Conscientiousness (b = .170, p-value = .000) was significantly associated with a higher intention to seek mental health help. Higher neuroticism also predicted higher mental health help-seeking intentions (b = .165, p-value = .001). On the other hand, openness, extraversion, and agreeableness did not predict such intentions. The results suggest that personal disposition could affect help-seeking intentions and that certain personality traits had more impact on these. It is hoped that the results will contribute to providing better mental health support for students and promote help-seeking.